Pengaruh Anemi Dan Indeks Masa Tubuh (IMT) Dengan Siklus Menstruasi Pada Mahasiswi D-III Kebidanan UNISLA - Wasiah, Asyaul; Kustini (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Throughout reproductive age, women will experience menstruation, and the average amount of blood lost in one menstrual period is around 50 cc. Adolescent girls are a high risk group for experiencing anemia. Someone with an overweight nutritional status tends to experience menstrual cycle irregularities. Anemia and nutritional status are factors that can influence menstruation. The research aims to determine the effect of anemia and Body Mass Index (BMI) on the menstrual cycle of UNISLA D-III Midwifery Students. This type of research is observational analytic with a cohort research design. Methods: This article This research was conducted at the UNISLA midwifery laboratory from February to April 2024. Initial data collection included measuring body weight and height, HB examination with easy touch and questionnaires. Determining the menstrual cycle by filling out a questionnaire about menstruation for the next 3 months. The research instruments used easy touch tools, scales, height meters and questionnaire sheets. The population in this study were students from the UNISLA D-III Midwifery study program. The sampling technique used in this research was total sampling with the number of samples used in this research being 51 samples. Data analysis uses a computer program with a confidence level of 95%. Bivariate analysis uses chi square with α 0.05. Multiple logistic regression was used to perform multivariate analysis Results: From the results of the logistic regression analysis, a significant value of p value = 0.463>0.05 was obtained for the anemia status variable and a significant value of p value =0.848>0.05 for the BMI variable, so it can be concluded that Ho is accepted or Ha is rejected, meaning that these two variables do not exist. influence on the menstrual cycle of D III Midwifery study program students Conclusion: The suggestions that can be given here are divided into two, namely for respondents and formal institutions such as schools. Respondents were advised to consume foods containing iron to increase hemoglobin levels so they could avoid anemia. Consuming nutritional needs to form blood such as. vitamin C, fruit and vegetables. Meanwhile, schools should be able to provide health knowledge about the importance of consuming foods that contain lots of iron, to avoid anemia